"I Can Speak English. But, I'm Shy." Self Record Videos Posted on WhatsApp Group towards Students Speaking Skill - Maghfiroh, Lailatul; Santoso, Dian Rahma (Linguistics and ELT Journal, 2024)
This study discusses self-recorded videos posted on WhatsApp group for 9 grade students at SMP Muhammadiyah 4 Porong. The purpose of this study was to determine the effect of self-recorded video posted on WhatsApp group towards students speaking skills in report text. The method used in this study was pre-experimental with quantitative research design using only one class. The instrument used in this study was a speaking test. The data were obtained from the pre-test and post-test results. By using paired sample T-test with SPSS, the result shows that there was a significant difference between pre-test and post-test. The average score for the pre-test was below the Minimum Completeness Criteria (KKM) in which the score was (49,5). Meanwhile, the average score of post-test was 75,0 passing the KKM indicator. It shows that there are differences in the score results. The means of the post-test score is higher than that of the pre-test. Based on the paired sample test, the results of using T-test, revealed that sig. (2-tailed) was 0.000, while alpha (α) was 0,05 (0,000<0,05). This indicates that Ho is rejected and Ha is accepted. The result shows that the use self-recorded videos posted on WhatsApp group has a significant effect in teaching speaking report text especially for students speaking skills.